2(6-6x)+7(x-7)=Ax+B

Simple and best practice solution for 2(6-6x)+7(x-7)=Ax+B equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6-6x)+7(x-7)=Ax+B equation:


Simplifying
2(6 + -6x) + 7(x + -7) = Ax + B
(6 * 2 + -6x * 2) + 7(x + -7) = Ax + B
(12 + -12x) + 7(x + -7) = Ax + B

Reorder the terms:
12 + -12x + 7(-7 + x) = Ax + B
12 + -12x + (-7 * 7 + x * 7) = Ax + B
12 + -12x + (-49 + 7x) = Ax + B

Reorder the terms:
12 + -49 + -12x + 7x = Ax + B

Combine like terms: 12 + -49 = -37
-37 + -12x + 7x = Ax + B

Combine like terms: -12x + 7x = -5x
-37 + -5x = Ax + B

Reorder the terms:
-37 + -5x = B + xA

Solving
-37 + -5x = B + xA

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1xA' to each side of the equation.
-37 + -5x + -1xA = B + xA + -1xA

Combine like terms: xA + -1xA = 0
-37 + -5x + -1xA = B + 0
-37 + -5x + -1xA = B

Add '37' to each side of the equation.
-37 + -5x + 37 + -1xA = 37 + B

Reorder the terms:
-37 + 37 + -5x + -1xA = 37 + B

Combine like terms: -37 + 37 = 0
0 + -5x + -1xA = 37 + B
-5x + -1xA = 37 + B

Reorder the terms:
-37 + -1B + -5x + -1xA = 37 + B + -37 + -1B

Reorder the terms:
-37 + -1B + -5x + -1xA = 37 + -37 + B + -1B

Combine like terms: 37 + -37 = 0
-37 + -1B + -5x + -1xA = 0 + B + -1B
-37 + -1B + -5x + -1xA = B + -1B

Combine like terms: B + -1B = 0
-37 + -1B + -5x + -1xA = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(37 + B + 5x + xA) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(37 + B + 5x + xA)' equal to zero and attempt to solve: Simplifying 37 + B + 5x + xA = 0 Solving 37 + B + 5x + xA = 0 Move all terms containing x to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + B + 5x + -37 + xA = 0 + -37 Reorder the terms: 37 + -37 + B + 5x + xA = 0 + -37 Combine like terms: 37 + -37 = 0 0 + B + 5x + xA = 0 + -37 B + 5x + xA = 0 + -37 Combine like terms: 0 + -37 = -37 B + 5x + xA = -37 Add '-1B' to each side of the equation. B + 5x + -1B + xA = -37 + -1B Reorder the terms: B + -1B + 5x + xA = -37 + -1B Combine like terms: B + -1B = 0 0 + 5x + xA = -37 + -1B 5x + xA = -37 + -1B The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 14/3+1/5t=7 | | 3(5x+6)=-12+15 | | 0=x^2-14x+24 | | 6u^3(-2u^5)= | | 0=8h^2+12h-4896 | | y=2x^2-x+2 | | 3x(x-9)=13x^2-28x | | 1=15t-5t^2 | | 3.6q-1.2-4.1q=-1.5q-5.1 | | (x^2+12x)+(3x^2+20)=180 | | 6w=3P-6l | | 9xsquared+4=12x | | 0=x^2-12x+11 | | 8(t-4)+4t=4(3t+3)-9 | | 7h+2h-5=19 | | 8x-4=5x+1 | | y=k(x-a)(x-b) | | 3+4x=2(2x+2) | | 4x^2+12X=160 | | -5y+6=-8y+12 | | 1.001/7=b | | x+x+17+2(x-30)=695 | | 11x+36=6x+6 | | 4/3*(3.14)*10^3 | | x+10x+25(33-2x)=182 | | 9xy-2y=-5 | | 11x-7+2x-3=10x-3+2x | | 2x-5+(3x+4)=5x-1 | | -16+-3x-16= | | -8x+4x-24=-28 | | 3-t/23+5=12 | | 4/3*(3.14)*1^3 |

Equations solver categories